Over-Expression of UV-Damage DNA Repair Genes and Ribonucleic Acid Persistence Contribute to the Resilience of Dried Biofilms of the Desert Cyanobacetrium Chroococcidiopsis Exposed to Mars-Like UV Flux and Long-Term Desiccation - Mosca, Claudia; Rothschild, Lynn J.; Napoli, Alessandro; Ferré, Fabrizio; Pietrosanto, Marco; Fagliarone, Claudia; Baqué, Mickael; Rabbow, Elke; Rettberg, Petra; Billi, Daniela (Frontiers in Microbiology, 2019)
The survival limits of the desert cyanobacterium Chroococcidiopsis were challenged by rewetting dried biofilms and dried biofilms exposed to 1.5×103 kJ/m2 of a Mars-like UV, after seven years of air-dried storage. PCR-stop assays revealed DNA lesions in dried biofilms and an increased accumulation in dried-UV-irradiated biofilms. Different types and/or amounts of DNA lesions were highlighted by a different expression of uvrA, uvrB, uvrC, phrA and uvsE genes in dried-rewetted biofilms and dried-UV-irradiated-rewetted biofilms, after rehydration for 30 min and 60 min. The up-regulation in dried-rewetted biofilms of uvsE gene encoding an UV-damage endonuclease, suggested that UV-damage DNA repair contributed to the repair of desiccation-induced damage. While the phrA gene encoding a photolyase, was up-regulated only in dried-UV-irradiated-rewetted. Nucleotide excision repair genes were over-expressed in dried-rewetted biofilms and dried-UV-irradiated-rewetted biofilms, uvrC gene showing the highest increase in dried-UV-irradiated-rewetted biofilms. Dried biofilms preserved intact mRNAs (at least of the investigated genes) and 16S ribosomal, suggesting that the persistence of the ribosome machinery and mRNAs might have played a key role in the early-phase recovery. Results have implications for the search of extra-terrestrial life by contributing to the definition of habitability of astrobiologically relevant targets such as Mars or planets orbiting around other stars.